Laminin γ-2 (LAMC2) promotes the proliferation and invasion of pancreatic cancer cells by regulating PI3K/Akt signaling - Qi Wang; Fusheng Zhang; Di Long; Weikang Liu; Yiran Chen; Yongsu Ma; Yinmo Yang; Zebin Mao; Xiaodong Tian (Journal of Pancreatology)
Background:. Pancreatic ductal adenocarcinoma (PDAC) poses a serious threat to human health with high mortality and poor prognosis, and there is an urgent need to explore the pathogenesis of PDAC in order to search for new therapeutic targets. Methods:. The expression of laminin γ-2 (LAMC2) in PDAC and its effect on the prognosis of tumor patients were predicted by an online database, and the expression level of LAMC2 in pancreatic cancer was verified by polymerase chain reaction (PCR) and western blot; flow cytometry, wound healing assay, Cell counting kit-8 (CCK8) assay, and colony formation assay were used to explore the effect of LAMC2 on the proliferation and migration of pancreatic cancer cells; and we also probed the potential relationship between LAMC2 and phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) signaling. Results:. High levels of LAMC2 in pancreatic cancer may benefit tumor proliferation migration and invasion and lead to poor prognosis of tumor patients. The mechanism by which LAMC2 promotes PDAC progression may be related to the activation of PI3K/Akt signaling to influence apoptosis and cell cycle. Conclusions:. LAMC2 promotes proliferation migration invasion of PDAC and leads to poor prognosis in pancreatic cancer patients.